EFFECT OF STEM DIAMETER, MEDIA TYPE AND LIGHT INTENSITY ON THE GROWTH OF MEDICINAL PLANT OF SCREW TREE/KAYU ULES (Helicteres isora Linn.) - Dani Pamungkas; Aziz Umroni; Nurhuda Adi Prasetyo (Indonesian Journal of Forestry Research, 2021)
Screw tree (Helicteres isora) is a shrub species (Fam: Malvaceae) with 1.5–4 m in height and  with multi-main trunks up to 9–12. In Indonesia, kayu ules has been used as a traditional medicine, known as jamu, and has been commercialized. In order to cultivate this species, vegetative propagation is likely promising compared to the generative propagation since seed viability is low and cannot be stored for longterm. Nevertheless, there is a lack of information on which diameter classes, media types and light intensities would give the best result for vegetative propagation. This research aimed to obtain information on which diameter classes and media that were suitable for kayu ules stem cutting propagation and to what degree the light intensity would be best for the growth of the seedlings of kayu ules. Three diameter classes and four media types were employed in a  complete random design under the greenhouse environment.   Three months old good quality vegetatively-propagated seedlings were transplanted under two light intensities (under transparent canopy and shading net). The result showed that  considering the factor of diameter classes and media in kayu ules stem cutting propagation, it had improved the survival of the stem cutting. Diameter class I was best grown in media type 3 with 46.67 ± 12.2 % of survival rate, diameter class II was best grown in media type 2 with 38.67 ± 11.6 % of survival rate, whereas diameter class III was best grown in media type 4 with 52 ± 6.9 % of survival rate. The transplanted seedlings also grew significantly better under transparent canopy with higher light intensity. The distinctive features of screw tree under shading net were wider leaf area, higher specific leaf area and relative water content but it was lower in above ground dry biomass compared to the kayu ules under transparent canopy.